An improvement of cultural practices to enhance lowland taro (Colocasia esculenta) yield in an acid sulphate soil in a rice ecosystem - Jayawardena, Senarath Nihal; Upasena, S.H.; Sumitra Poovarodom; Suthad Setboonsarng; United State Agency for International Development (USAID) (Bangkok : Asian Institute of Technology, 1991)
Four levels of nitrogen, three spacings and three source of nitrogen were tested for Taro (Colocasia esculenta) in a split-split plot design under irrigated condition at the Agriculture Research Farm of the Asian Institute of Technology in order to develop a suitable package of practices for nitrogen fertilizer and spacing management for the Taro farmers in Saraburi province of Central Thailand. The results revealed that the increase application of nitrogen increases the final tuber yield. The effect of nitrogen is mainly from corm and cormel weight and not for the increase of their numbers. The contribution of the spacing to the final tuber yield is highly significant and yield increase due to spacing is mainly due to the increase of number of corms and cormels per hectare. Among the three nitrogen sources tested Urea has shown the best performance in terms of the number as well as the weight of the corms and cormels. The nitrogen uptake of the crop has increased with the increased of N level; the overall N uptake of the Taro crop is 72.3 kg/ha. The leaf damage of Heliothis armiqera is influenced by the closer spacing and increase of N levels. However it seems to be more correlated with the weather conditions than the other factors.
A thesis submitted in partial fulfillment of requirement for the degree of Master of science
Thesis (M.Sc.) - Asian Institute of Technology, 1991
Keywords: Taro; Plants, Effect of soil acidity on